Pendidikan Masa Pendudukan Jepang: Studi pada Pendidikan Militer Pasukan Pembela Tanah Air - Lira, Rahmat Adnan; Ridhwan; Fatimah (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2024)
This study aims to analyze the impact of the military education policy implemented by Japan. Although intended to support their war efforts, this policy successfully ignited a spirit of nationalism and became a crucial factor in Indonesia’s struggle for independence. This research employs the historical research method. The data analysis process involves several steps: heuristics, historical criticism, interpretation, and historiography. The results indicate that the military education applied in Indonesia aimed to support Japan’s war efforts. However, this policy inadvertently sparked a sense of nationalism among Indonesian youth, leading to a strengthened movement for Indonesian independence. The formation of the Pasukan Pembela Tanah Air (PETA) was one significant policy that provided military training to Indonesian youth, who eventually became the backbone of the independence struggle. The strict educational practices of the Japanese successfully forged strong character and a spirit of resistance among the youth.